2020
DOI: 10.1080/15387216.2020.1780929
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Romania: transnational labour, geopolitics, and the Roma ‘outsiders’

Abstract: COVID-19 has played out in Romania in a similar way to that in many other European countries. The government implemented decisive early measures which were able to keep the infection and mortality rates relatively low. This paper considers three distinctive aspects of the situation in Romania. First, the situation was complicated by the influence of transnational migrant workers, large numbers of whom returned to Romania when the pandemic started, accounting for distinct geographical variations in the rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 27 publications
4
57
0
1
Order By: Relevance
“…They concluded that not only COVID-19 may have exacerbated pre-existing social disparities, but also has created new forms of inequalities, posing economic burdens for people living in epicenters, infected individuals, and families with COVID-19 patients. Similar arguments have been made by Creţan and Light (2020) and Krzysztofik et al (2020) in Romania and Poland, respectively. They argued that it is more likely for the poorest people and most marginalized regions to experience broader social and economic damages due to the pandemic.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…They concluded that not only COVID-19 may have exacerbated pre-existing social disparities, but also has created new forms of inequalities, posing economic burdens for people living in epicenters, infected individuals, and families with COVID-19 patients. Similar arguments have been made by Creţan and Light (2020) and Krzysztofik et al (2020) in Romania and Poland, respectively. They argued that it is more likely for the poorest people and most marginalized regions to experience broader social and economic damages due to the pandemic.…”
Section: Resultssupporting
confidence: 82%
“…They argued that it is more likely for the poorest people and most marginalized regions to experience broader social and economic damages due to the pandemic. Migrant workers are another vulnerable group that have been disproportionately affected ( Creţan and Light, 2020 ). Predicting a period of recession and rising unemployment in both Western and Eastern European countries, Creţan and Light (2020) pointed out that transnational employment opportunities may be dramatically reduced in Western Europe, while the recession may cause more Romanians to pursue work in other EU countries, and may also result in greater dependence among those who stay in the country on remittances sent by the migrant workers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The new "era of catastrophes" [12] is shaped by new and concatenated risks [13][14][15] in our unprecedented dynamic and interconnected world. The palette of the current crisis generated by COVID-19 pandemic is completed daily with new challenges whose complexity has never been encountered by humanity: the economic costs, as well as the heavy losses of human lives [16][17][18][19] are overlapped with major dysfunctions of health systems [20,21], transnational labor migration crisis [22,23], social stigma and racism [24,25], or geopolitical reassessments [26,27]. Even certain beneficial environmental impacts of the quasi-generalized outbreak of the 2020 spring have already been recorded [28][29][30], the governments will be faced with potential intersections and collisions of the current pandemic with other regional and global crises, generated especially by climatic and geopolitical stressors [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Everyone has tried to take advantage of globalization, where a cheap product has meant much-desired abundance and turned a blind eye to obvious social injustices: overworked employees, underpaid workers, and children working for a few pennies. This is the fertile soil in which pandemopolitics has been molded and which affects not only the states, but, especially, the poorest populations (Mayer and Lewis 2020, 17), whether they live in rich or less rich states (Creţan and Light 2020). In both the United States and France the highest mortality rates were recorded in the poorest cities and neighborhoods, heavily populated with marginalized and socially segregated people of color.…”
Section: Introductionmentioning
confidence: 99%